In-situ concrete industrial hardstandings specification, design, construction and behaviour - Knapton, John (Thomas Telford, 1999)
This book presents the first single source of detailed guidance for designers, specifiers and constructors of in-situ concrete industrial hardstandings. Despite the fact that in-situ concrete is used commonly as the construction material of industrial hardstandings, little guidance is available to the designer. In the past, industrial hardstandings have been engineered by adapting the methods and materials used in highways and industrial ground supported floors, often leading to the inappropriate use of materials and construction methods.